The Relationship between Static and Semi-Dynamic Balance with Accuracy and Speed of Direct Foot Kicks in Wushu Athletes - Hosein Bahram Tajari; Rasoul Nasiri Rad; Elaheh Azadian (Islamic Azad University, Hamedan Branch, 2023)
Objective The aim of this study was to investigate the relationship between static and semi-dynamic balance with the speed and accuracy of direct kicks in Wushu athletes. Methods This was a descriptive-correlational study. 25 Wushu athletes were selected through convenience sampling. Static balance was measured using the BESS test, which included three postures of standing with paired feet, single foot, and tandem, in two stable and unstable levels. Semi-dynamic balance was measured using the Star test. To measure the accuracy of foot strike landing and the speed of kicks, two wide and narrow colored tapes were used, and the number of correct kicks was divided by the execution time (20 seconds) for speed. SPSS software was used for data analyses at a level of significance of p< 0.05. The independent t-test was used to compare the effect of target width on the accuracy and speed of kicks, and the Pearson correlation was used to examine the relationship between the balance test scores and the accuracy and speed scores. Results In the paired feet posture on a stable surface, the number of errors was significantly less than it was in other postures (p < 0.05). The relationship between static balance and the speed of kicks was weaker than the relationship with accuracy (r < 0.05). The Star test showed a moderate and positive correlation (r < 0.05). Conclusion The lack of a significant relationship between static balance and the speed of kicks indicates differences in the underlying factors of these skills. On the other hand, there was a stronger relationship between static and semi-dynamic balance with the accuracy of kicks, which suggests that balance tests could be used as an assessment or training tool in talent identification centers or in the training of these individuals.